Plasmid-mediated virulence in Chlamydia - Turman, Breanna J.; Darville, Toni; O'Connell, Catherine M. (Frontiers in Cellular and Infection Microbiology, 2023)
Chlamydia trachomatis infection of ocular conjunctiva can lead to blindness, while infection of the female genital tract can lead to chronic pelvic pain, ectopic pregnancy, and/or infertility. Conjunctival and fallopian tube inflammation and the resulting disease sequelae are attributed to immune responses induced by chlamydial infection at these mucosal sites. The conserved chlamydial plasmid has been implicated in enhancing infection, via improved host cell entry and exit, and accelerating innate inflammatory responses that lead to tissue damage. The chlamydial plasmid encodes eight open reading frames, three of which have been associated with virulence: a secreted protein, Pgp3, and putative transcriptional regulators, Pgp4 and Pgp5. Although Pgp3 is an important plasmid-encoded virulence factor, recent studies suggest that chlamydial plasmid-mediated virulence extends beyond the expression of Pgp3. In this review, we discuss studies of genital, ocular, and gastrointestinal infection with C. trachomatis or C. muridarum that shed light on the role of the plasmid in disease development, and the potential for tissue and species-specific differences in plasmid-mediated pathogenesis. We also review evidence that plasmid-associated inflammation can be independent of bacterial burden. The functions of each of the plasmid-encoded proteins and potential molecular mechanisms for their role(s) in chlamydial virulence are discussed. Although the understanding of plasmid-associated virulence has expanded within the last decade, many questions related to how and to what extent the plasmid influences chlamydial infectivity and inflammation remain unknown, particularly with respect to human infections. Elucidating the answers to these questions could improve our understanding of how chlamydia augment infection and inflammation to cause disease.